Physicochemical characteristics, microbial safety and biological activities of fermented black sesame (Sesamum indicum L.) seeds dregs - Rosni, Nur Kamariah (2020)
Utilization of dregs has been widely used, especially in Indonesia, such as peanut dregs into local Indonesian food known as “oncom”. Sesame seed dregs are derived from the process of making sesame oil. The seed dregs were then proceeded with spontaneous fermentation for 7 days at room temperature (23- 27°C). During fermentation, physicochemical characteristics of the food product may undergo changes with microorganisms and bioactivities involvement in the process. The aims of this study were to analyse physicochemical characteristics and microbiological safety and quality of black sesame seed dregs during fermentation, to determine antimicrobial and antioxidant activity, and to identify bioactive compounds in raw black sesame seeds and fermented seed dregs extract. Physicochemical characteristics including internal temperature, pH value, total soluble solid (TSS), water activity (aw), colour determination, proximate analysis and texture profile analysis of seed dregs during fermentation were analysed using Association of Analytical Communities (AOAC) methods for food analysis. The present of microorganisms including total plate count (TPC), Escherichia coli, Salmonella spp., Pseudomonas aeruginosa, Bacillus cereus, Staphylococcus aureus, lactic acid bacteria (LAB), coliform bacteria, mould and yeast in seed dregs during fermentation were isolated using microbial selective media. The collected samples for analysis were raw seeds and seed dregs at day 0, 1, 3, 5 and 7 of fermentation. Raw seeds and fermented seed dregs (day 7) were extracted using water and ethanol and the extracts were further determined for antimicrobial activity against foodborne pathogens using Clinical and Laboratory Standard Institute (CLSI) methods. The total phenolic content was determined using a Folin-Ciocalteu assay and antioxidant activity was determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. The bioactive compounds in ethanol extract of raw seeds and fermented seed dregs were determined using Gas Chromatography-Mass Spectrometry (GC-MS) and Liquid Chromatography-Mass Spectrometry (LC-MS). The results showed that internal temperature, pH and TSS showed no significant differences while aw shows the significant increased from 0.53 to 0.92% during fermentation. The colour determination of final product had the highest lightness and yellowness but had the lowest redness. Moisture was significantly increased while ash, crude protein and carbohydrate were decreased and crude fat and fibre were showed no significant differences during fermentation. A gradually increased in hardness and decreased in springiness, chewiness and resilience were observed while cohesiveness showed no significant differences. Microbial counts were reduced in number of P. aeruginosa and B. cereus while increased in number of TPC, S. aureus, lactic acid bacteria, coliform bacteria and mould and yeast. The extraction yield using ethanol showed higher yield than water. Diameter of inhibition zones of extracts against 16 pathogenic microorganisms were in the ranged from 6.50 to 11.00 mm. Minimum inhibitory concentrations (MICs) of water extract were in the range from 3.13 to >50.00 mg/mL, mostly effective against B. cereus ATCC33019. Meanwhile, MICs of ethanol extract were in the ranged from 6.25 to 50.00 mg/mL, mostly effective against P. aeruginosa ATCC9027, B. megaterium ATCC14581 and C. albicans ATCC10231. Minimum bactericidal/fungicidal concentrations of water and ethanol were spread from 6.25 to >50.00 mg/mL and 25.00 to >50.00 mg/mL, respectively. Time-kill curve study showed S. aureus ATCC29737, E. coli ATCC43895 and B. cereus ATCC33019 were completely killed when exposed to ethanol extract of raw seeds and fermented seed dregs in 0.5 h incubation at 4× MIC. One hour had been taken to completely killed P. aeruginosa ATCC9027 and Candida albicans ATCC10231 after exposing to raw seeds extract while two hours had been taken after exposing to fermented seed dregs extract at 4× MIC. The fermented seed dregs extract showed higher total phenolic contents rather than raw seeds and seed dregs extracts. IC50 of the fermented seed dregs extract showed lower concentration than raw seeds and seed dregs extracts. There were 19 bioactive compounds in raw seeds and 24 compounds in fermented seed dregs extract detected by GC-MS including sesamin and sesamolin. Six compounds were identified to be the first time reported in sesame seeds by LC-MS which were cyclo(L-leucyl-L-prolyl), docosahexaenoic acid (DHA), enoxolone, α-eleostearic acid, 16-hydroxyhexadecanoic acid and oleanolic acid. In conclusion, there were changes on physicochemical characteristics during fermentation and fermented seed dregs had low level of microbial counts, rich of lactic acid bacteria and detected bioactive compounds were potentially good for antimicrobial and antioxidant activities.